PERK‐eIF2α‐ATF4‐CHOP Signaling Contributes to TNFα‐Induced Vascular Calcification. Issue 5 (5th September 2013) - Masuda, Masashi; Miyazaki‐Anzai, Shinobu; Levi, Moshe; Ting, Tabitha C.; Miyazaki, Makoto
Abstract : Background: Vascular calcification is a common feature in patients with chronic kidney disease (CKD). CKD increases serum levels of tumor necrosis factor‐α (TNFα), a critical mediator of vascular calcification. However, the molecular mechanism by which TNFα promotes CKD‐dependent vascular calcification remains obscure. The purpose of the present study was to investigate whether TNFα‐induced vascular calcification in CKD is caused by the endoplasmic reticulum response involving protein kinase RNA‐like endoplasmic reticulum kinase (PERK), eukaryotic initiation factor 2α (eIF2α), activating transcription factor 4 (ATF4), and C/EBP homologous protein (CHOP). Methods and Results: We examined the effects of TNFα on the endoplasmic reticulum (ER) stress response of vascular smooth muscle cells (VSMCs). TNFα treatment drastically induced the PERK‐eIF2α‐ATF4‐CHOP axis of the ER stress response in VSMCs. PERK, ATF4, and CHOP shRNA‐mediated knockdowns drastically inhibited mineralization and osteogenesis of VSMCs induced by TNFα. CKD induced by 5/6 nephrectomies activated the PERK‐eIF2α‐ATF4‐CHOP axis of the ER stress response in the aortas of ApoE −/− mice with increased aortic TNFα expression and vascular calcification. Treatment of 5/6 nephrectomized ApoE −/− mice with the TNFα neutralizing antibody or chemical Chaperones reduced aortic PERK‐eIF2α‐ATF4‐CHOP signaling of the ER stress increased by CKD. This resulted in the inhibition of CKD‐dependent vascular calcification. Conclusions: These results suggest that TNFα induces the PERK‐eIF2α‐ATF4‐CHOP axis of the ER stress response, leading to CKD‐dependent vascular calcification.